Development and validation of the mathematical model for synthesis of maleic anhydride from n-butane in a fixed bed reactor - Petrić, Ivan; Karić, Ervin (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2016)
The aims of this study were the following: development of themathematical model for numerical simulation of partial oxidation of n-butane to maleic anhydride in a fixed bed reactor and validation of developed mathematical model with real process data from industrial reactor located in the Global Ispat Coke Industry Lukavac. Mathematical model is consisted of differential equations that describe mass balances of each species, energy balance, stoichiometry of reactions, pressure drop, kinetic model. Numerical software package Polymath with Runge-Kutta-Fehlberg method was used for numerical solution of differential equations. The developed mathematical model was validated with three process data sets of five measured variables (temperature, pressure, concentration of n-butane, concentration of carbon dioxide, concentration of carbon monoxide) and with application of ten kinetic models from literature. Comparison of simulation results and measured data showed a good agreement for three kinetic models. For the chosen kinetic model, profiles of temperature, molar flows, conversion of n-butane and selectivity of maleic anhydride were also presented.